The utility of open-access biodiversity information in representing anurans in the Brazilian Atlantic Forest and Cerrado - Vasconcelos, Tiago S. [UNESP]; Nascimento, Bruno T. M. [UNESP] (My University, 2014)
Many geographic coordinates of species are only available in biological collections, and sometimes it is difficult to access these data. However, recent initiatives promise to compile and organize such biodiversity data at a global scale. We evaluated the effectiveness of open-access biodiversity information for forecasting the occurrence of anurans in two Brazilian hotspots - the Atlantic Forest (AF) and the Cerrado (CER). We compiled all available point-occurrence records for anuran species in both hotspots and identified the regions in each of the two hotspots having the highest and lowest number of anuran occurrences based on information from the Global Biodiversity Information Facility (GBIF) and the SpeciesLink project. A total of 13,130 point-occurrence records were recovered for 409 anurans from the AF (∼77% of the known species) and 12,729 records for 176 species (∼85% of the known species) from the CER. Density of point occurrence data is not randomly distributed within the hotspots. The greatest density of Atlantic Forest records is in southeastern Brazil, and the densest areas in Cerrado occur in the transitional zones to the Atlantic Forest. Comparison of these results with previous studies based on traditional museum information revealed that many important collections of anurans from these hotspots are not included in GBIF and SpeciesLink.
Keywords: Amphibians; GBIF; Point density analysis; SpeciesLink